2021
DOI: 10.21203/rs.3.rs-426888/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Autophagy Regulates the Effects of Adipose-derived Stem Cells Exosomes on Lipopolysaccharide-induced Pulmonary Microvascular Barrier Damage

Abstract: Background: Exosomes have been recognized as being more effective than direct stem cell differentiation into functional target cells for protecting against tissue injury and promoting tissue repair. Our previous study demonstrated the protective effect of adipose-derived stem cells (ADSCs) on lipopolysaccharide (LPS)-induced acute lung injury and the effect of autophagy on ADSC functions, but the role of ADSC-derived exosomes (ADSC-Exos) and autophagy-mediated regulation of ADSC-Exos in LPS-induced pulmonary m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that PMSC-Exos can improve myocardial damage 34 . Another study has con rmed that PMSC-Exos can improve the repair of pulmonary microvascular endothelial cell injury and increase the proliferation rate of endothelial cells 35 . However, no related studies of PMSC-Exos in the eld of POI are available.…”
Section: Discussionmentioning
confidence: 97%
“…Studies have shown that PMSC-Exos can improve myocardial damage 34 . Another study has con rmed that PMSC-Exos can improve the repair of pulmonary microvascular endothelial cell injury and increase the proliferation rate of endothelial cells 35 . However, no related studies of PMSC-Exos in the eld of POI are available.…”
Section: Discussionmentioning
confidence: 97%